STRATEGI PENGEMBANGAN BISNIS BERBASIS MENU ENGINEERING DI KAMBING SOON RESTO AND CAFE BANDUNG - Imam Ardiansyah; Vania Magdalena (Akademi Pariwisata Bunda Mulia, 2018)
ABSTRACT Bandung city is a tourist destination city that has a choice of various culinary both traditional and international. One of the Resto and Cafe in Bandung is Kambing Soon Resto and Cafe located at Jl. IR H Djuanda. One of the factors that become the main force for business in the field of this restaurant is the menu, even the menu can also be the identity of the restaurant terebut. A good menu can be seen from the level of sales and ability to provide benefits or the level of popularity and profitability. Based on these conditions, the researcher aims to analyze the engineering menu, the research was conducted in August 2017 until November 2017. The method used is the analysis of margin contribution and analysis of popularity index, menu classification, and SWOT analysis.Based on the analysis for 4 months, the results obtained are 32 food menu that the researcher carefully is the category of stars consists of 7 menus with percentage of 21.88%, plowhorses category consists of 11 menus with percentage of 34.37%, the category consists of puzzles 4 menus with percentage of 12.50%, dogs category consists of 10 menus with a percentage of 31.25%.Keywords: Menu Engineering, Business Development